Genistein alleviates chronic vascular inflammatory response via the miR-21/NF-κB p65 axis in lipopolysaccharide-treated mice - Xie, Xiaolin (Mol Med Rep, 2021)
Chronic vascular inflammatory response is an important pathological basis of cardiovascular disease. Genistein (GEN), a natural compound, exhibits anti-inflammatory effects. The aim of the present study was to investigate the effects of GEN on lipopolysaccharide (LPS)-induced chronic vascular inflammatory response in mice and explore the underlying anti-inflammatory mechanisms. C57BL/6 mice were fed with a high-fat diet combined with intraperitoneal injection of LPS to induce chronic vascular inflammation. The expression levels of TNF-α, IL-6 and microRNA (miR)-21 in the vasculature were detected via reverse transcription-quantitative (RT-q)PCR. The protein levels of inducible nitric oxide synthase (iNOS) and NF-κB p65 were detected via western blotting. NF-κB p65 was also analyzed via immunohistochemistry and immunofluorescence (IF). In addition, after transfection with miR-21 mimic or inhibitor for 24 h, vascular endothelial cells (VECs) were treated with GEN and LPS. RT-qPCR and western blot analyses were performed to detect the expression of TNF-α, IL-6, miR-21 and iNOS, and the protein levels of iNOS and NF-κB p65, respectively. IF was used to measure NF-κB p65 nuclear translocation. The results revealed that GEN significantly decreased the expression of inflammation-associated vascular factors in LPS-treated C57BL/6 mice, including TNF-α, IL-6, iNOS, NF-κB p65 and miR-21. Furthermore, miR-21 antagomir enhanced the anti-inflammatory effects of GEN. In LPS-induced VECs, miR-21 mimic increased inflammation-associated factor expression and attenuated the anti-inflammatory effects of GEN, whereas miR-21 inhibitor induced opposing effects. Therefore, the results of the present study suggested that GEN inhibited chronic vascular inflammatory response in mice, which may be associated with the inhibition of VEC inflammatory injury via the miR-21/NF-κB p65 pathway.